MOLECULAR BIOLOGY ANALYSIS OF IL -1Β, IL -4, AND IL -1Β RA GENE POLYMORPHISMS IN ETHNIC BASHKIR PATIENTS WITH RHEUMATOID ARTHRITIS, LIVING IN C HELYABINSK REGION - A. L. Burmistrova; D. S. Stashkevich; T. A. Susslova; I. V. Devald; A. O. Issakanova; O. N. Dimcheva (Медицинская иммунология, 2014)
Abstract. Common polymorphisms of interleukin-1β, receptor antagonist interleukin-1, and interleukin-4 genes have been studied among the patients with rheumatoid arthritis of Bashkir origin, living in Chelyabinsk Region. As a result of study, an increased frequency of interleukin-1β homozygosity for a high-producer allele was found. An association has been revealed between the homozygosity for 2-repeat allele of interleukin-4, and the age of disease onset.